The Impact of the Covid-19 Pandemic on the Capital Market in Indonesia (Indonesia Stock Exchange Composite (IDX) Case Study) - Tasya Rahmania; Rani Eka Arini; Yusuf Iskandar; Fitrina Lestari (Nusantara Science and Technology Proceedings, 2020)
The aim of this study is to (1) evaluate the effect of the Covid-19 pandemic on the growth of the Indonesian capital market (IDX); and (2) assess the influence of externalities and social distancing policies on the dynamics of the Indonesian capital market's progress. The case study approach is paired with a statistical research methodology that allows the use of dummy variables in multiple regression. The dependent variable is IDX, while the independent variables are the amount of Covid-19 instances in Indonesia, China, and Spain, the FTSE100 (London), Hangseng (Hong Kong), and NASDAQ (New York) stock indices, as well as differences in Indonesia's social distancing policies (Satgas, WFH and PSBB). According to the study's conclusions, both internal and external influences influenced the IDX's push. Inside Indonesia, the financial market has been impacted by the Covid-19 pandemic and social distancing policies. The Covid-19 pandemic in China and Spain had an impact on the ISHG index externally. Likewise, Hong Kong, London, and New York's capital markets.